2006
DOI: 10.3201/eid1209.060276
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Signatures of Human versus Avian Influenza A Viruses

Abstract: Fifty-two species-associated amino acid residues were found between human and avian influenza viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
257
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(265 citation statements)
references
References 35 publications
7
257
1
Order By: Relevance
“…Analysis of phenotypic markers showed that 040078‐H3N2 is a well‐adapted human virus containing several markers associated with high transmissibility in humans 25. Seven glycosylation sites were predicted for the H3 HA protein at positions 24, 38, 79, 149, 181, 301, and 499.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of phenotypic markers showed that 040078‐H3N2 is a well‐adapted human virus containing several markers associated with high transmissibility in humans 25. Seven glycosylation sites were predicted for the H3 HA protein at positions 24, 38, 79, 149, 181, 301, and 499.…”
Section: Resultsmentioning
confidence: 99%
“…As manual inspection of this volume of data is virtually impossible; it is necessary to use computational methods. Entropy (mutual-information)-based methods that use the amino acid frequency in each position are commonly used to this effect (27)(28)(29). These methods consider each position in the alignment separately, disregarding the possible relations between the sequence positions.…”
Section: Discussionmentioning
confidence: 99%
“…A single residue in the PB2 subunit of the influenza polymerase, amino acid 627, regulates polymerase activity in a species-specific fashion (5). PB2 derived from human viral isolates almost exclusively possesses a lysine at position 627 (K627), whereas glutamic acid (E627) at this position predominates in avian viruses (6). PB2 K627 correlates with enhanced polymerase activity, virus replication, transmission, and in certain cases, pathogenicity and mortality in mammals (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%